SPECIFICS OF FORMING SOCIAL COMPETENCE IN FUTURE PSYCHOLOGISTS (Psychology Travelogs, 2023)
In the article, an analysis of the phenomenon of social competence is conducted, highlighting its content, manifestations, and applications. Social competence is regarded as a complex and integrative characteristic of an individual, encompassing specific qualities, social skills, knowledge, experiences, emotional and value orientations, and personal beliefs that contribute to active interaction with society. The authors of the article examine the process of socialization and criteria for its formation, emphasizing the importance of mastering specific knowledge, skills, and abilities necessary for interaction in society. The development of social competence is determined by content-cognitive, communicative, behavioral, emotional-volitional, and motivational indicators. Special emphasis is placed on the role of social competence in psychologists, viewing it as a dynamic and complex structure. Psychology students should cultivate skills for the psychological analysis of client personalities, monitoring conditions of personal development, identifying psychological diagnoses, and conducting psychological correctional measures. Structural components of a psychologist's social competence include motivational, emotional-volitional, functional, communicative, and reflexive aspects. Developed social competence in psychologists is a key factor in successful psychological practice and effective relationships with clients. The formation of social competence is crucial for both individual personalities and society as a whole. The process of active socialization, adaptation, and interaction of an individual with the surrounding environment determines their successful functioning in a social context. Due to the intricate synthesis of cognitive, subject-practical, and personal experience, competence emerges as a product of self-development, personal growth, and the generalization of activity and personal experience. Considering this, professional education becomes highly motivated and person-oriented, facilitating the maximum utilization of personal potential.
Keywords: social competence; future psychologists; components of social competence; psychological characteristics of social competence; formation of social competence